Kombinasi Penggunaan Model Warna Dalam Pendeteksian Letak Bibir pada Gambar digital Berwarna - Sulaeman Santoso; Erico Darmawan Handoyo (Maranatha University Press, 2015)
Different color model has been used to detect the location of lips within color images. These color models have different advantages and weakness. This paper intends to compare several uses of color model (namely the rgb, normalized rbg, and the YCbCr color model that is used frequently on several lip localization technique) and try to propose a combination of color model to minimize post processing in lip localization. The proposed combination combines the normalized rgb color model, the YcbCr colod model and the intensity based rgb model to obtain lip area. The combination proved to provide better distinction with only slighty more calculation.